2016
DOI: 10.1111/1365-2664.12834
|View full text |Cite
|
Sign up to set email alerts
|

Do grazing intensity and herbivore type affect soil health? Insights from a semi‐arid productivity gradient

Abstract: Grazing is one of the most widespread forms of intensive management on Earth and is linked to reductions in soil health. However, little is known about the relative influence of herbivore type, herbivore intensity and site productivity on soil health. This lack of knowledge reduces our capacity to manage landscapes where grazing is a major land use. 2. We used structural equation modelling to assess the effects of recent (cattle, sheep, goats, kangaroos and rabbit dung) and historic (cattle, sheep/goat livesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 44 publications
5
81
1
4
Order By: Relevance
“…Soils are dominated by clay loams and loams. Sites were selected from a total pool of 451 where vegetation, soils and grazing intensity data had previously been collected (Eldridge, Delgado‐Baquerizo, Travers, Val, & Oliver, ). Sites were selected to span the available range of grazing intensities (see below) and habitat conditions (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Soils are dominated by clay loams and loams. Sites were selected from a total pool of 451 where vegetation, soils and grazing intensity data had previously been collected (Eldridge, Delgado‐Baquerizo, Travers, Val, & Oliver, ). Sites were selected to span the available range of grazing intensities (see below) and habitat conditions (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…We used algorithms, developed previously for the study area (see Eldridge, Delgado-Baquerizo, et al, 2016) to calculate the total oven-dried mass of dung per hectare per herbivore based on the number of pellets recorded in the field. we considered a number of small fragments to have originated from one dung event if the fragments were within an area of a few metres.…”
Section: Quantitative Determination Of Degradation Status and Grazimentioning
confidence: 99%
“…While this might at first sound counterintuitive, and is contrary to our hypothesis, it is consistent with the observation that grazing increases the cover of annual, high biomass exotic forbs such as Echium plantagineum . Belsky & Blumenthal, 1997;Eldridge et al, 2011;Eldridge, Delgado-Baquerizo, et al, 2016;Fleischner, 1994;Jones, 2000). Our SEM also indicated that grazing reduced soil health, consistent with a large number of studies globally (e.g.…”
Section: Herbivore Effects On Hydrologymentioning
confidence: 99%
“…wild animals (Wallis de Vries et al, 2007) and soil microorganisms (Eldridge et al, 2017b;Olivera et al, 2016), and alters multiple soil physicochemical properties that determine soil health (Eldridge et al, 2017a). Overgrazing is also considered to be a major driver of desertification in terrestrial ecosystems (Cherlet et al, 2018).…”
mentioning
confidence: 99%